2007
DOI: 10.1007/s00203-007-0229-6
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of diurnal and vertical microbial diversity of a hypersaline microbial mat

Abstract: Microbial mats are prokaryotic communities that provide model systems to analyze microbial diversity and ecophysiological interactions. Community diversity of microbial mat samples was assessed at 8:00 a.m. and 3:00 p.m. in a combined analysis consisting of 16S rRNA-denaturing gradient gel electrophoresis (DGGE) and phospholipid fatty acid (PLFA) profiles. The divergence index determined from PLFA and DGGE data showed that depth-related differences have a greater influence on diversity than temporal variations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…Our observations do show some difference from the past studies. A recent publication using phospholipid fatty acid analysis and denaturing gradient gel electrophoresis to characterize depth‐related population structure of another hypersaline mat (Camargue, France) (Caumette et al , 1994) suggested that microniches were more important than time of day in determining community structure (Villanueva et al , 2007). This contrasts with our data showing that, although depth stratification was clearly an important factor, time of day explained the majority of the variation in T‐RFLP profiles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our observations do show some difference from the past studies. A recent publication using phospholipid fatty acid analysis and denaturing gradient gel electrophoresis to characterize depth‐related population structure of another hypersaline mat (Camargue, France) (Caumette et al , 1994) suggested that microniches were more important than time of day in determining community structure (Villanueva et al , 2007). This contrasts with our data showing that, although depth stratification was clearly an important factor, time of day explained the majority of the variation in T‐RFLP profiles.…”
Section: Discussionmentioning
confidence: 99%
“…Morphology, a principle tool used in those past identifications, is well known to conceal diversity. Molecular analyses are being increasingly used to characterize community structure in mats (Risatti et al, 1994;Ward et al, 1998;Mouné et al, 2003;Casillas-Martinez et al, 2005;Fourçans et al, 2006;Desnues et al, 2007;Villanueva et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…2). It is assumed, based on previous work (Villanueva et al, 2007) that depth-related differences in structure are more important than diel variations in controlling the distribution of microorganisms.…”
Section: Microbiology and Palynologymentioning
confidence: 99%
“…In turn, 18:4x3 pointed to the presence of diatoms. In another study, Villanueva et al (2007) observed the daily migrations of micro-organisms in an intertidal hypersaline microbial mat in France. They reported that the total PLFAs that indicated the maximum viable biomass were the highest at the top of the mat in the morning hours, while in the afternoon the highest volume was found underneath the uppermost layers.…”
Section: Microbial Diversity In Biomatsmentioning
confidence: 99%